(NiSSLEDOWANIQ STROENIQ(B, (NTEPLOWOGO DWIVENIQ I SWOJSTW VIDKOSTEJ (B:s (NsBORNIK STATEJ (B/s - (N{AHPARONOW(B, (NmIHAIL iWANOWI^s; (NfILIPPOW(B, (Nl(B.(Np(B.s ((NmOSKWA (B:s (Nmgu(B,s, 1986)
(NbIBLIOGR(B. (NW KONCE ST(B.s
Keywords: (NvIDKOSTIs; (NfIZIKO(B-(NHIMI^ESKIE SWOJSTWAs